Sedimentary Characteristics and Evolution Controlling Factors of Platform Margin Reef-Shoal: A Case Study of Upper Carboniferous-Middle Permian in Wushi Area, Tarim Basin. (11th May 2022) - Sun, Ke; Lin, Huixi; Wang, Guanmin; Chen, Qinghua; Zhang, Jibiao
Abstract : Upper Carboniferous-Middle Permian platform margin reef-shoal reservoirs are one of the most important exploration targets for the northwestern margin of Tarim Basin. In order to obtain a clear understanding of the controlling factors for the platform margin reef-shoal development, field outcrops in the Wushi area, northwestern margin of Tarim Basin had been studied in this article by field measurements, thin section identification, carbon and oxygen isotope testing, and ancient provenance analysis. Studies have shown that the platform margin reefs in the Wushi area were dominated by algae reefs, and the platform margin shoals are dominated by bioclastic shoals and gravel shoals. The characteristics of algal bind inside grains were common. During the Zhaerjiake period, interbedded reefs and shoals were the main type, and platform marginal reefs were of the progressive type. During the Balediertage period, huge thick platform margin reefs were the main type, and the platform margin reefs were of accretion-weak progressive type. The development controlling factors of the platform margin reef-shoal are mainly relative sea-level change, palaeosource, and paleogeomorphy. Relative sea-level changes controlled the development characteristics and superposition mode of the platform margin reef-shoal; there were two sides of the influence of the palaeosource on the platform margin reef-shoal; the paleogeomorphology controlled the development position and spreading scale of platform margin reef-shoal. In the covering area, the platform margin reef-shoal reservoirs adjacent to the fault zone and with large sedimentary thickness might have a good prospect for hydrocarbon exploration.